The effect of green practice activities on the understanding of green technology topics in the secondary school Geography curriculum - Mohamad Pirdaus Yusoh; Nuralia Husna Rosli; Mazdi Marzuki; Jabil Mapjabil; Nurhazliyana Hanafi; Mohd Norazmi Nordin; Harniyati Hussin; Nor Hidayati Idris (International Journal of Special Education (IJSE), 2022)
This study aims to analyze the levels of,and differences between,the effects of variables related togreen practice activities on the understanding of green technology topics in the Form 2 Geography curriculum in SekolahMenengahKebangsaan Seri Aman, Johor. A quantitative approach with a survey and questionnaire design was used in this study, whichsampled152 Form 2 and 3 students using a simple random sampling technique. Descriptive analysis (frequency, percentage, mean, and standard deviation) and inferential analysis (t-test and ANOVA) were used to answer the study questions. The findings of the study showed that the high level of effects(M = 3.95, SP = .78). The t-test results showed no significant difference between the effects based on age t (152) = .279, p> .05. The results of the t-test showed a significant difference between the effects based on gender t (152) = .001, p <.05. The results of ANOVA did not show any significant difference between the effects based on the grade obtained in theGeography subject F (2.352) = .057, p> .05. In conclusion, this study shows that students weregreatly affected bythe impactsofgreen practice activities. The study also makesrecommendations to improve the implementation of green practice activities. The Ministry of Education Malaysia can usethis study as a reference and encourage all schools to implement green practice activities so that love for the environment can be applied and the students' understanding of environmental topics,such as green technology, canincrease.